2008
DOI: 10.4103/0970-4388.40320
|View full text |Cite
|
Sign up to set email alerts
|

Greenstick fracture of the mandible: A case report

Abstract: This case report is an insight in to pediatric traumatology whereby bilateral greenstick fracture of condyle is used as a means to discuss the incidence and anatomic considerations for the management of the same, highlighting the fact that dental surgeons require a unique understanding of the anatomy, growth considerations, healing pattern and operative management involving minimal manipulation while managing pediatric facial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
1
16
0
3
Order By: Relevance
“…Most mandibular condylar fractures involve the condylar neck, with a few reports of intracapsular fractures. 22 Direct impact usually leads to a unilateral fracture because the weak condylar neck breaks easily, 23 and there is no intracranial displacement. 24 In this study, the nature and location of the fractures, being bilateral, strongly suggested that the condylar fractures were caused by indirect forces transmitted to the condyles from a blow to the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Most mandibular condylar fractures involve the condylar neck, with a few reports of intracapsular fractures. 22 Direct impact usually leads to a unilateral fracture because the weak condylar neck breaks easily, 23 and there is no intracranial displacement. 24 In this study, the nature and location of the fractures, being bilateral, strongly suggested that the condylar fractures were caused by indirect forces transmitted to the condyles from a blow to the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Pediyatrik kemik kırıkları özel bir patolojidir, çünkü bu hızla büyüyen kemikler üzerinde gerçekleşir.…”
Section: -5unclassified
“…The anatomical level of the condylar fracture is divided into three sites: the condylar head (intracapsular), the condylar neck (extracapsular) and the subcondylar region [4]. Although the condyle is well protected in the glenoid fossa, its neck is a relatively fragile area [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the condyle is well protected in the glenoid fossa, its neck is a relatively fragile area [5]. The subcondylar fracture, which was associated with a green-stick fracture, is usually seen at the age of less than 6 years due to the fact that a child’s bone is more flexible, so that it can be more likely bent rather than a complete breakage [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation